Recovery of neurofilament following early monocular deprivation - O'Leary, Timothy P.; Kutcher, Matthew R.; Mitchell, Donald E.; Duffy, Kevin R. (Frontiers in Systems Neuroscience, 2012)
A brief period of monocular deprivation in early postnatal life can alter the structure of neurons within deprived-eye-receiving layers of the dorsal lateral geniculate nucleus. The modification of structure is accompanied by a marked reduction in labeling for neurofilament, a protein that composes the stable cytoskeleton and that supports neuron structure. This study examined the extent of neurofilament recovery in monocularly deprived cats that either had their deprived eye opened (binocular recovery), or had the deprivation reversed to the fellow eye (reverse occlusion). The degree to which recovery was dependent on visually-driven activity was examined by placing monocularly deprived animals in complete darkness (dark rearing). The loss of neurofilament and the reduction of soma size caused by monocular deprivation were both ameliorated equally following either binocular recovery or reverse occlusion for 8 days. Though monocularly deprived animals placed in complete darkness showed recovery of soma size, there was a generalized loss of neurofilament labeling that extended to originally non-deprived layers. Overall, these results indicate that recovery of soma size is achieved by removal of the competitive disadvantage of the deprived eye, and occurred even in the absence of visually-driven activity. Recovery of neurofilament occurred when the competitive disadvantage of the deprived eye was removed, but unlike the recovery of soma size, was dependent upon visually-driven activity. The role of neurofilament in providing stable neural structure raises the intriguing possibility that dark rearing, which reduced overall neurofilament levels, could be used to reset the deprived visual system so as to make it more ameliorable with treatment by experiential manipulations.